2017
DOI: 10.1038/modpathol.2016.178
|View full text |Cite
|
Sign up to set email alerts
|

P53 expression correlates with poorer survival and augments the negative prognostic effect of MYC rearrangement, expression or concurrent MYC/BCL2 expression in diffuse large B-cell lymphoma

Abstract: In patients with diffuse large B-cell lymphoma, MYC rearrangement (MYC-R), MYC expression, or concurrent expression of MYC and BCL2 is associated with a poorer prognosis. P53 expression also has been shown to confer inferior survival in diffuse large B-cell lymphoma patients, but less is known about the role of P53 expression in those with MYC-R, MYC expression (MYC+), or MYC&BCL2 co-expression (MYC+/BCL2+). We studied P53 expression in 201 patients with untreated de novo diffuse large B-cell lymphoma. Sixty-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 37 publications
3
56
1
Order By: Relevance
“…The cutoffs for CD10, BCL6, and MUM1 positivity were 30% as used in the Hans algorithm [26]. The positive cutoffs for MYC, BCL2, and P53 expression were ≥40%, ≥50%, and ≥50% of cells, respectively, as have been reported previously [21,[27][28][29][30][31].…”
Section: Immunophenotypingmentioning
confidence: 70%
See 2 more Smart Citations
“…The cutoffs for CD10, BCL6, and MUM1 positivity were 30% as used in the Hans algorithm [26]. The positive cutoffs for MYC, BCL2, and P53 expression were ≥40%, ≥50%, and ≥50% of cells, respectively, as have been reported previously [21,[27][28][29][30][31].…”
Section: Immunophenotypingmentioning
confidence: 70%
“…Previous studies have shown that P53 expression can enhance the negative effect of MYC translocation and expression [40,41]. In earlier studies, P53 overexpression was shown to augment the negative prognostic effect of MYC/BCL2 double hit lymphoma and MYC/BCL2 double expression lymphoma [28,30]; in other words, P53 expression is a poor prognostic factor in MYC/BCL2 double hit lymphoma. In this study, P53 expression was observed in 29% of triple hit lymphoma cases evaluated and was associated with an inferior overall survival compared to cases without P53 overexpression (p = 0.04), similar to the negative impact of P53 reported in MYC/ BCL2 double hit lymphoma.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…8 MYC can also paradoxically lead to the repression of apoptosis by increasing the expression of the tumor suppressor TP53. [9][10][11] To overcome this scenario, MYC requires the contribution of other genetic events (eg, the expression of BCL2 and mutations in TP53) to promote Cancer December 15, 2018 proliferation and oncogenesis. 8 The spectrum of MYC effects appears dependent on the histologic context; for example, transcriptional targets in Burkitt lymphoma (BL) are completely distinct from transcriptional targets in DLBCL even though they share an identical t (8;14) rearrangement.…”
Section: Mycmentioning
confidence: 99%
“…Staining for p53 protein was uniformly strong in the tumor, correlating well with the presence of mutations. Expression of p53 in de novo DLBCL was shown to be correlated with inferior outcome [20, 21]. In addition to TP53 mutations, FISH studies of the patient's tumor showed deletion of TP53 in 14/100 cells and monosomy of chromosome 17 in 20/100 cells (Figure 3).…”
Section: Discussionmentioning
confidence: 99%